Numerical Simulation and Experimental Study on Flow of Polymer Aqueous Solution in Porous Jet Nozzle - Minghui Wei; Chenghuai Wu; Yanxi Zhou (Advances in Polymer Technology)
The addition of a polymer to the jet medium enhances its ability to break rock, and the structure of the nozzle plays a vital role in the full utilization of energy. In this paper, a self-propelled porous jet bit with a support plate is designed, which can prevent the drill bit from jamming due to the jet nozzle against the bottom of the well during the drilling process. And the structural design of the cone-converging nozzle is applied to the forward center nozzle. The polymer additive jet flow field and the pure water jet flow field were compared by numerical simulation and experimental investigation. The results show that the polymer additive jet has a longer isokinetic core, and the rock-breaking volume of the polymer additive jet is much larger than that of the pure water jet, and the optimal spray distance is increased. The forward central jet with the conical convergent nozzle structure has more efficient rock-breaking ability.